PENGARUH INSENTIF, DISIPLIN KERJA, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN BAGIAN SEWING PT. PELITA TOMANGMAS KARANGANYAR - Yeri Yuliyanti, Istiatin, Ida Aryati (ITB AAS INDONESIA, 2017)
The purpose of this research are: 1) To determine the effect of incentive, dicipline, and comunication simultaneously on employee performance sewing division PT.Pelita Tomangmas Karanganyar. 2) To determine the effect of incentive, dicipline, and comunication on employee performance sewing division PT.Pelita Tomangmas Karanganyar..Data collection method used is the method of questionnaire / questionnaire to 50 employees as respondents. Sampling technique used is random sampling method convenionce sampling. Data analysis methods used include: test instrument (validity and reliability), hypothesis testing (multiple linear regression analysis, t-test, f and the coefficient of determination (R2).Results Descriptive analysis showed that most respondents gender female (90%). All data from the questionnaires have passed the test instrument. For testing f test result that the value of F (46.710)> F table (2,81) with a probability of 0.000 (p <0.05). This means Fhitung in the region of Ho rejected, which means a significant difference between the independent variable (incentive, dicipline, and comunication) simultaneously on the dependent variable (employee performance). From the results of the t test result incentive have a significant positive effect on an individual basis to variable employee performance. This is evident from tcount (5.697)> t table (2.013) with a significance value <α (0.05). Variable dicipline are also significant positive effect on employee performance. This is because tcount (2.164)> t table (2.013) with a significance value <α (0.05). comication is also significant positive effect on employee performance. This is because tcount (2,551)> t table (2.013) with a significance value <α (0.05). The results of the analysis in this study was obtained R2 values of 0.753 (75.3%). This means that the independent variable (incentive, dicipline, and comunication) able to contribute 75.3% influence on the dependent variable (employee performance). While the rest of 24.7% is influenced by other variables outside of this study as a leadership, compensation, organisational culture, working environment, etc.Keywords: Incentive, dicipline, comunication, employee performance